Performance analysis of optimum receivers for fast frequency-hopped systems over composite interference and fading channels with imperfect side information - Le, Ly Minh Duy (2014)
A fast frequency-hopped (FFH) system has an efficient anti-interference capability and is robust against fading. The performance of FFH systems is mainly affected by the intentional or unintentional interference, additive white Gaussian noise, timing and frequency offsets, as well as fading channels. The interference can be mitigated or avoided by hopping the carrier frequency of the transmitted signal over a wide bandwidth in a pseudorandom pattern. Fading channels can cause a significant degradation in the performance of a communication system. The concept of diversity methods for fading channels was therefore introduced in the literature. Diversity methods have been shown to help overcome the performance degradation caused by fading channels. In practice, the two commonly encountered interference models against the FFH systems are partial-band noise interference (PBNI) and multitone interference (MTI). Hence, it is essential to investigate the composite effect of PBNI and MTI on FFH systems over fading channels. The analytical bit-error rate expressions are derived for FFH M-ary frequency-shift-keying (MFSK) maximum-likelihood (ML) receivers under the composite effect of MTI and PBNI over either frequency-nonselective Rician fading or frequency-selective Rayleigh fading channels. The ML structures are also proposed and analyzed. The numerical results show that the proposed systems can effectively suppress the composite interference effect over fading channels. In practical systems, it is well known that there always exists time and frequency mismatch between the transmitter and the receiver. Based on the log-likelihood ratio criterion, a ML receiver for FFH/MFSK systems is proposed to combat the composite effect of PBNI and MTI with the presence of timing and frequency offsets over frequency-nonselective Rayleigh fading channels. Analytical bit-error rate (BER) expression for the proposed receiver is derived and validated by simulations. Comparing with other existing diversity-combining receivers such as the linear-combining and product-combining receivers, the proposed receiver achieves the best performance at the expense of system complexity. In addition, the sensitivity of system performance to imperfect side information is also examined. The effect of multiple-access interference (MAI) on the performance of FFH multiple-access (MA) systems is investigated. The analysis of FFH-MA systems over frequency-selective Rayleigh fading channels is first performed, followed by the frequency-selective Rician fading. For the case of frequency-selective Rayleigh fading, the exact closed-form expression of the characteristic function of the ML decision variable will be derived. For the case of frequency-selective Rician fading, we derive the probability density function (pdf) of the ML decision variable. Following that, the discrete convolution approach will be applied to obtain the pdf of the final decision statistics. Our analysis shows that the proposed ML receivers can suppress the MAI more effectively than the conventional receivers, i.e., up to two orders of magnitude in the BER performance improvement.